Primary versus secondary intraocular lens implantation in traumatic cataract after open‐globe injury in pediatric patients. Issue 12 (December 2018) - Sen, Pradhnya; Shah, Chintan; Sen, Alok; Jain, Elesh; Mohan, Amit
Abstract : Purpose : To compare the visual and refractive outcomes and complications of primary and secondary intraocular lens (IOL) implantation after open‐globe injury in pediatric patients. Setting : Sadguru Netra Chikitsalaya, Madhya Pradesh, India. Design : Retrospective case series. Methods : Patients had primary cataract extraction with IOL implantation with globe repair (Group A) or repair followed by secondary IOL implantation (Group B). Preoperative and surgery data, visual outcomes, and postoperative complications were recorded. Results : The study included 139 patients. Thirty (49%) of 61 patients in Group A and 47 (60%) of 78 patients in Group B achieved a corrected distance visual acuity (CDVA) of 20/40 or better. In both groups, a central corneal scar and amblyopia were the main reasons for not achieving a CDVA better than 20/40. The mean spherical equivalent (SE) was 1.81 diopters (D) in Group A and 1.55 D in Group B. Forty patients (66%) in Group A and in 60 patients (77%) in Group B achieved a desirable refractive outcome (SE <2.00 D). A large wound was the greatest risk factor for not obtaining desirable refractive outcomes. Fibrinous uveitis was the most common postoperative complication in both groups. Pupillary optic capture and IOL decentration were significantly more common in Group A than in Group B ( P = .02), while strabismus was significantly more common in Group B ( P = .04). Conclusions : Both approaches had satisfactory and comparable visual and refractive outcomes. However, primary IOL implantation can be considered in cases with small peripheral corneal lacerations with the goal of providing early visual rehabilitation and avoiding repeat general anesthesia.